Pengembangan Bahan Ajar Berbasis Grafis dan Matematis Model ADDIE Pada Pembelajaran Teori Ekonomi Mikro - Astri Srigustini; Iis Aisyah (Universitas Negeri Padang, 2023)
This study aims to develop teaching materials that use mathematical and graphical approaches so as to improve the learning outcomes of Economics Education students. The method used in the preparation of microeconomic teaching materials is the ADDIE model development method (Analyze, Design, Develop, Implement, Evaluate). This graphic and mathematical-based microeconomic teaching material is applied to three classes of microeconomic theory courses in 2022. The results of the research at the student needs analysis stage found that most students were still constrained in learning microeconomics in the graphics and calculation sections, most of them needed a more concise and detailed book for the discussion of curves and calculations. The design stage, namely the validation of the content of economic material carried out by experts, has a feasibility percentage of 73%. The development stage is carried out by readjusting the Sub-CPMK and graphic and mathematical approach material. The implementation stage is carried out in 3 classes for 14 meetings. The evaluation stage is carried out by UTS with an average completeness of learning outcomes of 73% and UAS as much as 89% of 103 students.